Burden of Stroke Caregivers: Evidence from a Qualitative Study in Sarawak, Malaysia - Rahman, M. M.,; Suut, N.,; Putit, Z.,; Arif, M. T.,; Said, A. B.,; Suhaili, M. R. B.,; Fadzillah, M.,; AkBakon, F.,; Tambi, Z. binti,; Kee, L. H. (Ibn Sina Trust, 2024)
Background: Stroke survivors experience long-term physical, psychosocial and cognitive impairment that are formidable challenges to caregivers because caring for stroke survivors needs explicit knowledge and caregivers have to endure the stressfulness as a result of caring. In addition, little is known about perceived benefits of the stroke care giving experience.